Analisis Pertimbangan Hakim Pengadilan Agama Kelas 1 A Kota Jambi dalam Putusan No. 642/Pdt.G/2020/PA.Jmb tentang Perceraian Sebab Hypersex - Muhammad Hilal Madeli; Illy Yanti; Sulaeman Sulaeman (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
In a marriage, things often happen that make the relationship tenuous and even lead to divorce. Divorce has various reasons, one of which is divorce due to hypersex/having sex out of the ordinary. Divorce case in Decision Number 642/Pdt.G/2020/PA.Jmb., in which the plaintiff reported the defendant because of disputes and quarrels between the two because one of the reasons the defendant has hypersex. Because of this report, the judge granted the plaintiff's request for divorce from the defendant, based on the law and the results of the judge's ijtihad. This study aims to reveal the judge's considerations in granting the plaintiff's lawsuit and explore the sources of law that are used as the basis by the judge in deciding the case. This research is a library research that focuses on the judge's decision and examines related books and adds interviews with the judge who decides the case. This study found that the basis for judges in making decisions is to use two legal instruments, namely statutory regulations and books of fiqh. Article 116 letter (e) Compilation of Islamic Law) which emphasizes that between husband and wife there are continuous disputes and fights and there is no hope of living in harmony in the household again. Then referring to the explanation of article 39 of Law no. 1 of 1974, one of the parties has a disability or illness which causes them to be unable to carry out their obligations as husband/wife, as well as the book Manhaj al-Thullab, page 346.